1984
DOI: 10.1203/00006450-198411000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness of the Pituitary-Testicular Axis to Gonadotropin-releasing Hormone and Chorionic Gonadotropin during the First Week of Life

Abstract: ABSTRACT. Qualitative changes are known to occur in testicular steroidogenesis at birth as the testosterone peak is reached without significant elevation of basal luteinizing hormone in the 2nd wk of life. This study was designed to evaluate testicular activity prior to these changes. Pituitary-testicular function was studied by measuring serum gonadotropins and steroids after stimulation by gonadotropin-releasing hormone (GnRH) (one intravenous injection) and human chorionic gonadotropin (hCG) (three intramus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…The absent relation between SHBG and non‐SHBG‐T in our subjects implies that the observed testosterone levels are not just the result of an unleashed HPG axis but are restrained by the feedback inhibition of non‐SHBG‐T. This is supported by the observation that LH and/or testosterone secretion in neonates can be further increased when stimulated with GnRH or human chorionic gonadotropin 19 . Although the HPG axis is operative in neonates, circulating (non‐SHBG) T levels are much lower than in adults.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The absent relation between SHBG and non‐SHBG‐T in our subjects implies that the observed testosterone levels are not just the result of an unleashed HPG axis but are restrained by the feedback inhibition of non‐SHBG‐T. This is supported by the observation that LH and/or testosterone secretion in neonates can be further increased when stimulated with GnRH or human chorionic gonadotropin 19 . Although the HPG axis is operative in neonates, circulating (non‐SHBG) T levels are much lower than in adults.…”
Section: Discussionsupporting
confidence: 62%
“…This is supported by the observation that LH and/or testosterone secretion in neonates can be further increased when stimulated with GnRH or human chorionic gonadotropin. 19 Although the HPG axis is operative in neonates, circulating (non-SHBG) T levels are much lower than in adults. It appears that the higher SHBG levels found in neonates are not responsible for the relatively low levels of non-SHBG-T. A different setpoint of the HPG axis in neonates might thus be postulated.…”
Section: Newbornsmentioning
confidence: 99%
“…Low testosterone production and poor response to stimulation with hCG had already been reported in SLOS (15). This is not expected, since it has been reported that positive response to hCG stimulation is found in normal prepubertal boys at any age (10), including the first week of life (16). The histology of the testes was normal for age, and there was no evidence of testicular dysgenesis.…”
Section: Discussionmentioning
confidence: 73%